An Analysis of the Determinants of Work Productivity among Production Employees at PT. Putra Wijaya Production - Ni Kadek Yuliandari; Sinta Tri Lestari (FOUNDAE (Foundation of Advanced Education), 2025)
Work productivity is often considered an important indicator in evaluating employee performance, particularly in the production sector where consistent achievement of operational targets is expected. PT. Putra Wijaya Production, a company engaged in screen printing and garment services, appears to face challenges in sustaining and enhancing employee productivity amid growing industry competition. This study aims to examine the relationship between transformational leadership, work discipline, and intrinsic motivation on the work productivity of production employees at PT. Putra Wijaya Production. A quantitative approach was employed to analyze the influence among variables. Work productivity was measured by the employees’ ability to meet company targets through the optimal use of time, effort, and skills. The sample consisted of 35 respondents selected using purposive sampling, with inclusion criteria of a minimum one-year tenure and at least 90% attendance. Data were analyzed using SPSS software. The findings suggest that transformational leadership, work discipline, and intrinsic motivation collectively have a significant effect on work productivity. However, work discipline was not found to have a direct individual effect. These results indicate that while discipline remains important, transformational leadership and intrinsic motivation may have a more substantial role in improving employee productivity. The study implies that companies could benefit from focusing on developing inspirational leadership styles and fostering employees’ intrinsic motivation as part of their productivity enhancement strategies.